Don't Bite the Hand that Feeds: Rebel Funding Sources and the Use of Terrorism in Civil Wars. - Fortna, Virginia Page; Lotito, Nicholas J; Rubin, Michael A (International Studies Quarterly, 2018)
Why do some rebel groups resort to terrorism tactics while others refrain from doing so? How rebel organizations finance their rebellion creates variation in the extent to which terrorism undermines their legitimacy. Rebel organizations pay attention to the legitimacy costs associated with terrorism. Organizations that rely primarily on civilian support, and to a lesser extent on foreign support, exercise more restraint in their use of terrorism. Rebels who finance their fight with lootable resources such as gems or drugs are least vulnerable to the costs of alienating domestic supporters. Thus, they are more likely to resort to terrorism and to employ more of it. The article elaborates this legitimacy-cost theory and tests it using new data on Terrorism in Armed Conflict from 1970 to 2007. We find robust support for the hypothesis that groups who finance their fight with natural resources are significantly more likely to employ terrorism (though not necessarily to conduct more deadly attacks) relative to those who rely on local civilian support. Groups with external sources of financing, such as foreign state support, may be more likely to engage in terrorism than those who rely on local civilians, but not significantly so.